Experimental electromagnetic compatibility of conducted electromagnetic interferences from an IGBT and a MOSFET in the power supply - Lahlaci, M. E.; Miloudi, M.; Miloudi, H. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2024)
Introduction. Most electromagnetic compatibility studies carried out in the context of power switch research are generally valid for low frequencies. This frequency restriction appears to be too restrictive for a complete analysis of the electromagnetic interference conducted. The novelty of this work lies in the load-dependent an optimal selection of IGBTs and MOSFETs for least-disturbance power switching in the frequency range from 150 kHz to 30 MHz, based on an optimal experimental selection procedure and show the impact of load value on switch switching and noise generation. Purpose. Analysis of the fundamental possibility of selecting a switching device with a power supply based on an experimental measurement which allows to increase the reliability of the entire mechanism operation and significantly simplify the design. Methods. In this paper, the proposed study is used and compared with experimental results at low and high frequencies. Then, a comparison is made for conducted electromagnetic interference (common-mode and differential-mode) generated by IGBT and MOSFET for different loads, and the proposed methodology is verified on an experiment suitable for predicting terminal overvoltage analysis and conducted electromagnetic interference problems. Practical value. The primary method for establishing a conducted electromagnetic interference source for switching devices is based on IGBT and a MOSFET depending on the resistive load. References 22, figures 17.